Selective element fission approach for fast FEM simulation of incremental sheet forming based on dual-mesh system - Zhang, M. H.; Lu, B.; Chen, J.; Long, H.; Ou, H. (Springer, 2015)
Incremental sheet forming (ISF) is a highly versatile and flexible process for producing low batches of sheet metal parts. Although finite element (FE) method is a key approach in the study of material deformation in metal forming processes, the application of FE in ISF process is still limited. This is due to the enormous simulation time required for ISF processes. Focusing on this problem, this paper presents a new selective element fission (SEF) approach for simulation of ISF process based on LS-DYNA. In the approach, the computational efficiency is improved by reducing the unnecessary calculations of elements outside the localized deformation zone in the ISF process. The introduction of a background mesh for simulation data storage and a separate simulation mesh with varied mesh density for simulation ensures both the efficiency of computation and accuracy of results. To verify the proposed SEF method, two ISF case problems including a hyperbolic cone part and a pyramid part are studied by comparing to the conventional FE approach and the H-adaptive approach in terms of the CPU time, the forming load, the final part profile, and thickness distribution. The influence of two key factors: element size ratio and toolpath segment length is also studied. The results suggested that the developed SEF approach can save the CPU time by up to 74 % with satisfactory accuracy as compared to conventional FE method, which demonstrates both the effectiveness and robustness of the developed SEF approach.